Mupirocin Promotes Wound Healing by Stimulating Growth Factor Production and Proliferation of Human Keratinocytes - Twilley, Danielle; Reva, Oleg; Meyer, Debra; Lall, Namrita (Frontiers in Pharmacology, 2022)
Mupirocin has been reported for its role in the treatment of infected wounds through its antibacterial activity, however the role of mupirocin in promoting wound healing via alternative mechanisms has not been extensively evaluated. This study aimed to evaluate the potential effect of mupirocin to promote wound healing, not only through its antibacterial activity but by increasing human keratinocyte proliferation and growth factor production. In the scratch assay, using human keratinocytes (HaCat), mupirocin (at 0.1 and 0.2 mM) significantly increased wound closure compared to the vehicle control. Cell viability, measured from the scratch assay, verified the increase in wound closure, where mupirocin at both concentrations showed higher cell viability compared to the vehicle control. In addition, mupirocin at 0.1 mM significantly stimulated the production of HGF and M-CSF in HaCat cells, whereas at 0.2 mM, PDGF-AA and EPO were increased. The findings of this study suggest that mupirocin, which is commonly used as an antibacterial agent for the treatment of wounds, also facilitates the wound healing process by stimulating the proliferation of human keratinocytes and enhancing the production of several growth factors involved in wound healing. This is the first report on the effect of mupirocin on growth factors expressed by human keratinocytes as well as the stimulation of keratinocyte proliferation.